Evaluate the effectiveness of tonsillectomy and long-acting penicillin on the levels of the antistreptolysin O titer in children with recurrent tonsillitis - Kumar, Alekh; Kumari, Nupur (International Journal of Research in Medical Sciences, 2019)
Background: Tonsillitis is widespread among children and has serious poststreptococcal complications, and both the patients and clinician have to face the question on what is the role and benefit of using long-acting penicillin and whether it is an alternative method of treatment to surgery?. This study was carried out to evaluate the effectiveness of tonsillectomy compared with long-acting penicillin in the treatment of recurrent tonsillitis, comparing their effects on the levels of the antistreptolysin O titer (ASOT). Methods: A total of 100 patients aged 4-15 years with recurrent tonsillitis and signs of chronic tonsillitis, after exclusion of patients with bleeding diathesis, anemia, chronic illness, and criteria of rheumatic fever, were included in this study, they were divided to two groups comprising 50 patients each. The first group was treated by tonsillectomy, whereas the second group was treated using long-acting penicillin monthly for 6 months. They were clinically evaluated, ASOT levels were recorded for all patients before management and after 6 months. Results: The mean ASOT readings before management and after 6 months for the tonsillectomy group were 518.29 and 117.13 IU/ml, respectively (P value <0.004), whereas for the penicillin group, they were 526.70 and 262.98 IU/ml, respectively (P value <0.072). Conclusions: This study demonstrates that the first line of treatment of recurrent chronic tonsillitis is tonsillectomy, as it is both clinically effective and cost-effective for children and that the second line of treatment is long-acting penicillin with a long-term follow-up and in patients have contraindications for surgery such as bleeding diathesis.